Gall midges Cecidomyidae (Diptera) common in Ukraine, their trophic connections and harmfulness - Cherniy, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
Information is given on the common cecidomyiidae phytophagous cultures in agricultural crops. The morphological signs, biological features of development, trophic bundles of gallstones are indicated. Characterization of the most harmful species is Mayetiola destructor Say, Sitodiplosis mosselana Gehin, Stenodiplosis panici Plotn., Contarinia tritici Kirby, C. Medicagine Kieffer, C. pisi Winnertz, C. pyrivora Riley, Dasineura floralis Maric., Dasineura mali Kieffer, D. pyri Bouche D. Obtain Rubs., D. ribis Barnes, D.plicatrix Loew., Thomasiniana oculiperla Rubs., T. ribis Marik., Lasioptera rubi Schrank. Covered periods of their development and harmfulness. Described are characteristic signs of damages by cerebellum corn and leguminous cultures, perennial legumes and fruit and berry plantations.